Personality homophily drives female friendships in a feral ungulate - Debottam Bhattacharjee; Kate J. Flay; Alan G. McElligott (iScience)
Summary: Similarity or homophily in personality drives preferential strong social bonds or friendships in humans and some non-human primate species. However, little is known about the general behavioral “decision rules” underlying animal friendships in other taxa. We investigated a feral and free-ranging population of water buffalo (Bubalus bubalis) to determine whether homophily in personality drives female friendships (n=30) in this social ungulate. Close spatial proximity served as an indicator of friendship, validated by affiliative body contact. A “bottom-up” method revealed three personality traits – social tension, vigilance, and general dominance. We found that individuals with lower personality differences (i.e., more similar) in social tension and general dominance traits exhibited higher spatial associations, suggesting that friendships in buffalo can form based on personality homophily. Our findings offer crucial insights into the role of personalities driving complex social patterns in species beyond primates.